PENERAPAN TEKNIK ICEBREAKER JENIS GAMES DAN GERAK BADAN UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN ELEKTROKIMIA DI KELAS X TSM 1 SMK NEGERI 5 PEKANBARU - Annisa Fitri; Susilawati '; Elva Yasmi Amran (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is a classroom action research. This classroom action research is an effort to improve the learning process of chemistry of class X students of TSM 1 SMK N 5 Pekanbaru by applying the Icebreaker type of learning technique of games and bodybuilding. This study aims to improve students' learning motivation. This study was conducted in two cycles, each cycle consisting of two meetings covering four stages of implementation, namely: planning, implementation, observation and reflection. Data collection techniques used questionnaires, observations, and tests. The technique of data analysis is done descriptively using percentage technique. Based on the results obtained, it can be concluded that the use of Icebreaker learning techniques can improve students' learning motivation. This can be seen from the increase of learners motivation from 70% in cycle I to 77,67% in cycle II.Key Words : The Icebreaker technique type of Games and Bodybuilding, Learning motivation